2017
DOI: 10.3892/ijo.2017.4012
|View full text |Cite
|
Sign up to set email alerts
|

Staging performance of whole-body DWI, PET/CT and PET/MRI in invasive ductal carcinoma of the breast

Abstract: The aim of the present study was to evaluate the performance of whole-body diffusion-weighted imaging (WB-DWI), whole-body positron emission tomography with computed tomography (WB-PET/CT), and whole-body positron emission tomography with magnetic resonance imaging (WB-PET/MRI) in staging patients with untreated invasive ductal carcinoma of the breast. Fifty-one women with newly diagnosed invasive ductal carcinoma of the breast underwent WB-DWI, WB-PET/CT and WB-PET/MRI before treatment. A radiologist and a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Similar findings of improved detection of osseous breast cancer metastases with PET/MRI vs. PET/CT were described in a series of 65 bone metastases in 17 patients with recurrent breast cancer by Sawicki et al In a study by Catalano et al, PET/MRI identified significantly more breast cancer metastases to bone compared with PET/CT (141 vs. 90, P < 0.001) in 25 patients . Catalano et al also reported significantly improved whole‐body staging in 51 patients with invasive breast cancer using PET/MRI vs. PET/CT (50/51 vs. 38/51 correct, P < 0.01) …”
Section: Distant Metastasessupporting
confidence: 67%
“…Similar findings of improved detection of osseous breast cancer metastases with PET/MRI vs. PET/CT were described in a series of 65 bone metastases in 17 patients with recurrent breast cancer by Sawicki et al In a study by Catalano et al, PET/MRI identified significantly more breast cancer metastases to bone compared with PET/CT (141 vs. 90, P < 0.001) in 25 patients . Catalano et al also reported significantly improved whole‐body staging in 51 patients with invasive breast cancer using PET/MRI vs. PET/CT (50/51 vs. 38/51 correct, P < 0.01) …”
Section: Distant Metastasessupporting
confidence: 67%
“…In a similar approach, Catalano et al [27] found that wholebody PET/MR was more accurate in correctly predicting the initial stage of breast cancer than whole-body DWI MRI, but the discrepancies were not statistically significant (p = 0.14). Another study [28] evaluated the diagnostic performance of PET/MR for axillary nodal staging and found that PET/MR changed the staging in 22% of patients compared with PET/ CT.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Sawicki et al [19], whole-body 18 F-FDG PET/MRI reported superiority regarding detection of distant malignant lesions compared to whole-body MRI in recurrent breast cancer patients. Catalano et al [38] compared whole-body 18 F-FDG PET/MRI with whole-body DWI MRI in a smaller cohort study, yielding an insignificantly better performance of PET/MRI in predicting the initial wholebody tumor stage of breast cancer.…”
Section: Discussionmentioning
confidence: 99%